THEORETICAL PRINCIPLES AND PROSPECTS OF USING MODELS OF FUNCTIONING OF SOCIALLY RESPONSIBLE BUSINESS - Romanovska, A.; Velichko, V. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers the features, disadvantages and advantages of existing models of socially responsible business. The state of socially responsible business in Ukraine is also analyzed, the main obstacles to development are identified. Based on the results obtained, ways to overcome obstacles and prospects for dissemination are proposed. The main incentives for the implementation of CSR would be the introduction of preferential taxation, reducing administrative pressure on local authorities and providing them with proposals for social development programs in the region. In the context of globalization of the modern market, an increasing number of large enterprises in developed countries are paying attention to issues of socially oriented business. Corporate citizens, along with their core business activities, carry out activities aimed at solving social, environmental and other problems in the community. Corporate social responsibility is beginning to be used as one of the indicators of ensuring the competitiveness of the enterprise. Such changes in the socio-economic environment require a more detailed analysis of the criteria of socially responsible and socially oriented business to build an effective model of operation of the entity. In world practice, there are several models of socially responsible business, due to national and cultural characteristics of doing business. They correspond to three models of corporate governance. These are American, European and Japanese models. These models of CSR are quite common and are based on the cultural traditions of countries, economic and environmental situation. As for Ukrainian enterprises, companies do not perceive CSR as a policy that is integrated into the company’s business strategy and is a factor of competitive advantage in the market. To develop CSR, it is necessary to develop a legal framework that would promote these activities, raise awareness of responsible business behavior, introduce CSR courses in university programs and increase the participation of business associations in promoting practices.